Development and assessment of a novel gold immunochromatographic assay for the diagnosis of schistosomiasis japonica - Mu, Yi; McManus, Donald P.; Gordon, Catherine A.; You, Hong; Ross, Allen G.; Olveda, Remigio M.; Cai, Pengfei (Frontiers in Immunology, 2023)
Background: The neglected zoonosis, schistosomiasis japonica, remains a major public health problem in the Philippines. The current study aims to develop and evaluate the performance of a novel gold immunochromatographic assay (GICA) for the detection of Schistosoma japonicum infection. Methods: A GICA strip incorporating a S. japonicum saposin protein, SjSAP4 was developed. For each GICA strip test, diluted serum sample (50 µl) was loaded and strips were scanned after 10 min to convert the results into images. ImageJ was used to calculate an R value, which was defined as the signal intensity of the test line divided by the signal intensity of the control line within the cassette. After determination of optimal serum dilution and diluent, the GICA assay was evaluated with sera collected from non-endemic controls (n = 20) and endemic individuals living in schistosomiasis-endemic areas of the Philippines (n = 60), including 40 Kato Katz (KK)-positive participants and 20 subjects confirmed as KK-negative and faecal droplet digital PCR assay (F_ddPCR)-negative at a dilution of 1:20. An ELISA assay evaluating IgG levels against SjSAP4 was also performed on the same panel of sera. Results: Phosphate-buffered saline (PBS) and 0.9% NaCl were determined as optimal dilution buffer for the GICA assay. The strips tested with serial dilutions of a pooled serum sample from KK-positive individuals (n = 3) suggested that a relatively wide range of dilutions (from 1:10 to 1:320) can be applied for the test. Using the non-endemic donors as control, the GICA strip showed a sensitivity of 95.0% and absolute specificity, while using the KK-negative and F_ddPCR-negative subjects as control, the immunochromatographic assay had a sensitivity of 85.0% and a specificity of 80.0%. The SjSAP4-incorperated GICA displayed a high concordance with the SjSAP4-ELISA assay. Conclusions: The developed GICA assay exhibited a similar diagnostic performance with that of the SjSAP4-ELISA assay, yet the former can be performed by local personnel with minimal training with no requirement for specialised equipment. The GICA assay established here represents a rapid, easy-to-use, accurate and field-friendly diagnostic tool for the on-site surveillance/screening of S. japonicum infection.